Investigating the influence of tourism on economic growth and climate change: The case of Croatia - Hafezali Iqbal Hussain; Abdul Razak Abdul Hadi (Contemporary Economics, 2019)
In Croatia, tourism is one of the most important economic activities, accounting for 2.1% of total tourist flows in the European Union and 18% of the total Croatian gross domestic product. Economic development and tourism flows are influenced by the increasing intensity of climate change, leading to a need to adapt to new business conditions to minimize the negative and maximize the positive effects. The objective of the current study is to empirically research the role of tourism in the Croatian economy for the period 2004-2015 and the impact of climate change on tourist flows. To investigate experts' opinions on the impact of climate change on Croatian tourism, this study employs a qualitative approach to obtain comprehensive insights into tourism, climate change and scientific research. By conducting in-depth interviews with experts and identifying the challenges posed by the current impact of climate change on Croatian tourism, the authors gain deeper insights into tourism development and climate change that reflect the current situation in Croatia. The results indicate that climate change will not have a negative impact on Croatian tourism in the near future. However, after 2050, a number of adaptation measures will be required to maintain the current tourism status.
Keywords: A10; O20; Q50; Q58; 330; economic development; tourism; climate change; Croatia